Fluids Intake and Beverage Consumption Pattern among University Students - Jamal Ghaemmaghami; Reza Mahdavi; Elnaz Faramarzi; Sima Balaghi (Tabriz University of Medical Sciences, 2011)
Background: Insufficient and inappropriate daily fluid intake in a long period may have adverseeffect on human's health. Therefore, the present study evaluated the amounts and sources of fluidsconsumed by university students to determine whether these amounts and sources of fluid wereenough and appropriate.Methods: In this descriptive study, 245 (142 females and 103 males) volunteer students of TabrizUniversity of Medical Sciences in 2009 were recruited. Food and fluid intake of subjects were assessedby 24-hour recall method of 3 days (two week days and one week- end included). Dietaryintake of subjects was analyzed by Nutritionist III software program. The mean total fluid intake(drinking fluid values merged with data on the water content of foods) and the rate of metabolicwater were figured out. Comparisons of the results with recommended dietary values were madeusing student's t-test.. Data of dietary intakes for two under-reporter female subjects were notincluded in the statistical analysis.Results: Daily total mean of fluid intake for girls (1598±40ml) and boys (1861±59ml) reflect thesum of beverages (Girls, 818±29ml; boys, 1147±57ml) and food water (Girls, 780±47ml; boys,714±86m). The most consumed beverage for girls and boys were water (40%) and tea (49%)respectively. Daily mean intake of milk for girls and boys were 106.31±10ml (13%) and57.30±11ml (5%), respectively.Conclusion: The mean daily fluid intake of subjects, specially water, and milk was lower than recommendedvalues. Therefore, there is an urgent need for tailored nutrition intervention targetingthe young adults to improve their beverage choices.